2015
DOI: 10.1074/jbc.m115.673459
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of CalS8, a TDP-α-d-Glucose Dehydrogenase Involved in Calicheamicin Aminodideoxypentose Biosynthesis

Abstract: Background:The biosynthesis of deoxypentoses appended to bacterial secondary metabolites is poorly understood. Results: Characterization of CalS8, a putative sugar dehydrogenase in calicheamicin biosynthesis, reveals unique base permissivity with a bias toward TDP-glucose. Conclusion: CalS8 contains a modified intersubunit loop implicated as the substrate specificity factor in this prototype dehydrogenase. Significance: This work presents a new blueprint for base specificity annotation among putative UGDHs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…It has often been reported that S. albus J1074 produces only aglycones when the BGCs of glycosylated metabolites are heterologously expressed. We speculate that S. albus J1074 lacks the gene encoding UDP-glucose 6-dehydrogenase (UGDH), as this enzyme has been known to convert UDP-glucose to UDP-glucuronic acid, , which is also not present in BGC-18. However, the heterologous production of the aglycones in S. albus confirms that compounds 1 – 3 are the metabolic products of BGC-18 (renamed the Acd cluster, Table S9), thus allowing us to propose the biosynthesis of 1 – 3 (Figure B).…”
Section: Results and Discussionmentioning
confidence: 99%
“…It has often been reported that S. albus J1074 produces only aglycones when the BGCs of glycosylated metabolites are heterologously expressed. We speculate that S. albus J1074 lacks the gene encoding UDP-glucose 6-dehydrogenase (UGDH), as this enzyme has been known to convert UDP-glucose to UDP-glucuronic acid, , which is also not present in BGC-18. However, the heterologous production of the aglycones in S. albus confirms that compounds 1 – 3 are the metabolic products of BGC-18 (renamed the Acd cluster, Table S9), thus allowing us to propose the biosynthesis of 1 – 3 (Figure B).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the de novo biosynthesis of dTDP-D-GlcA, dTDP-D-Glc was oxidized by dTDP-D-Glc dehydrogenase to give dTDP-D-GlcA. [45] We cloned and tested several reported dTDP-D-Glc dehydrogenases, but the activities were not good for use in large-scale synthesis. Thus, we tried to prepare dTDP-D-GlcA by salvage synthesis.…”
Section: Methodsmentioning
confidence: 99%